2018
DOI: 10.1080/15548627.2018.1425059
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-dependent transcriptional induction of lethal autophagy: A new perspective for cancer treatment

Abstract: Dendrogenin A (DDA) is a mammalian metabolite that displays anticancer and chemopreventive properties in mice. At the cancer cell level, DDA induces differentiation and death. We investigated herein the nature of DDA cytoxicity in cancer cells. We showed that DDA triggers biochemical and cellular features of macroautophagy/autophagy and that autophagy is cytotoxic. DDA induces both the accumulation of pro-lysosomal sterols and stimulates the expression of regulators of autophagy such as NR4A, LC3 and TFEB thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Interestingly, in tumor cells, the natural steroid Dendrogenin A has been shown to stimulate expression of Nur77 via binding to LXRβ and induce lethal autophagy ( 91 , 92 ), opening up new perspectives for cancer treatment ( 93 ). Moreover, it has been shown that Dendrogenin A, in addition to inducing growth control and improve overall survival in mice, also induces immune cell infiltration, including DCs, in the tumor ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in tumor cells, the natural steroid Dendrogenin A has been shown to stimulate expression of Nur77 via binding to LXRβ and induce lethal autophagy ( 91 , 92 ), opening up new perspectives for cancer treatment ( 93 ). Moreover, it has been shown that Dendrogenin A, in addition to inducing growth control and improve overall survival in mice, also induces immune cell infiltration, including DCs, in the tumor ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of melanoma cells treated with THPN, a chemical compound targeting NR4A1, cell death occurs after induction of excessive mitophagy, due to NR4A1 translocation to the inner membrane of the mitochondria, causing dissipation of mitochondrial membrane potential by the permeability pore complex ANT1/VDAC [14]. Furthermore, Dendrogenin A, a mammalian cholesterol metabolite ligand of liver-X-receptors (LCRs) induces Nr4a1 expression in association with excessive autophagic cell death both in vitro and in vivo [15,16], displaying anticancer and chemopreventive properties in mice [17]. Interestingly, NR4A1 interaction with anti-apoptotic BCL2 family members outside the BH3 domain induces autophagic cell death [18], which seems to be mediated by releasing BECN1 in a model of cigarette smokeinduced autophagic cell death [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of melanoma cells treated with THPN, a chemical compound targeting NR4A1, cell death occurs after induction of excessive mitophagy, due to NR4A1 translocation to the inner membrane of the mitochondria, causing dissipation of mitochondrial membrane potential by the permeability pore complex ANT1/VDAC (14). Furthermore, Dendrogenin A, a mammalian cholesterol metabolite ligand of liver-X-receptors (LCRs) induces Nr4a1 expression in association with excessive autophagic cell death both in vitro and in vivo (15, 16), displaying anticancer and chemopreventive properties in mice(17). Interestingly, NR4A1 interaction with anti-apoptotic BCL2 family members outside the BH3 domain induces autophagic cell death (18), which seems to be mediated by releasing BECN1 in a model of cigarette smoke-induced autophagic cell death(19).…”
Section: Introductionmentioning
confidence: 99%